In silico analysis of active metabolites isolated from Libidibia ferrea Martius (Research, Society and Development, 2020)
The present work carried out in silico studies to predict the pharmacokinetic, physicochemical, toxicological and biological activities of isolated metabolites from Libidibia ferrea Martius, a plant popularly used for the treatment of inflammations and injuries, such as antidiabetic, antimicrobial, antifungal and antileishmaniasis. Comparisons were made using the following programs: chemsketch, mcule property calculator, preadmet, protox and pass online. The results revealed that only the molecules lupenone and trans-farnesol showed intestinal absorption above 90%. The metabolites gallic acid, catechin, methyl-gallate, quercetin and trans-farnesol follow the rule of lipinsk in all its preconditioned parameters. With regard to enzyme inhibition, each of the study molecules demonstrated inhibition directed at at least two CYP enzymes. Lupenone was the only molecule that was active against the protozoan leishmania, in addition to being promising against neoplasms and inflammation. Catechin and quercetin demonstrated positive results with regard to antioxidant activity, and most of the substances in the study in question showed mucomembranous protection capacity. No substance demonstrated embryotoxicity or teratogenesis, but all molecules were found to have a certain level of toxicity in other analysis parameters. In pharmacokinetic, toxicological and biological terms, pauferrol A, B and C molecules were the least promising, while lupenone, catechin and quercetin showed the best results.